Status of Pasil Reef Marine Sanctuary in Cogtoug Bay. Philippines - Tuyogon, Tertuliano C. (JPAIR Multidisciplinary Research, 2008)
The status of corals and reef fish resources inside Pasil ReeJ Marine Sanctuary in Cogtong Bay, Bohol, Philippines was surveyed using 50m Lille Intercept Transect method to obtain percent coral cover. The coral reef fish populations in the sanctuary were assessed using Fish Visual Census along 50m transect covering 2 coral communities separated by 2 depth gradients (2m and 10m.). Benthic life forms intercepted by the transects were recorded and identified in situ. A similar census was also conducted outside the Marine Protected Area (MPA) to serve as controls. The results showed that in both areas live hard massive corals dominate. However, live hard and soft coral Cover was significantly higher inside (the sanctuary than outside. The difference of coral structure inside and outside the sanctuary was analyzed through independent sample I-test and the result showed that there was no significant difference. The results of the present survey was compared with a survey conducted two years ago and it showed that the percent live coral cover and fish populations inside and outside the sanctuary significantly increased. Friedman's tests revealed that the abundance of fish population in the MPA between 2003 and 2005 were statistically significant. The researcher concluded that the implementation of Posit Reef Marine Sanctuary indeed positively impacted the biological parameters of the sites
Keywords: marine sanctuary; corals; benthic; marine protected area; in situ